Ventriloquizing the South: Reading Melville across the Civil War - FURUI, YOSHIAKI (Journal of American studies, 2024)
Cody Marrs’s concept of “transbellum literature” has urged critics to reconsider the position of the Civil War that neatly divides literary history into “antebellum” and “postbellum.” Marrs’s idea encourages us to see both continuity and discontinuity between the postbellum and antebellum periods. Taking as a main subject of inquiry Herman Melville’s “Lee in the Capitol” in Battle-Pieces , one of the poems written from the perspective of the South, I would like to inquire into what the South as a geographical and political entity meant to Melville after the Civil War. In this poem, Melville gets inside Robert E. Lee’s inner psyche, ventriloquizing his suppressed emotions. By ventriloquizing Lee, Melville can be seen as doing violence to the alterity of the South in ways that conflict with his representation of others in his antebellum fiction. This essay interrogates how the Civil War changed Melville’s approach to representing alterity by focussing on the presence of the South as a geographical other in Battle-Pieces . At the heart of this perceived change lies his concern with representing community rather than individuals. However, Melville ultimately finds himself othered from the southern individuals, thereby demonstrating less discontinuity than continuity in terms of his ethics of alterity.